The Missouri State Penitentiary : 170 years inside the walls - Rasmussen, Jamie Pamela (Missouri heritage readers., 2012)
Asked how the Missouri State Penitentiary compared to other famous prisons, a historian and former prison administrator replied, "It's older and meaner." For 168 years, it was everything other prisons were and more. In The Missouri State Penitentiary, Jamie Pamela Rasmussen recounts the long and fascinating history of the place, focusing on the stories of inmates and the struggles by prison officials to provide opportunities for reform while keeping costs down. Tales of prominent prisoners, including Pretty Boy Floyd, Sonny Liston, and James Earl Ray, provide intrigue and insight into the institution's infamous reputation.